Tinjauan Deskriptif Aspek Ergonomi Tata Ruang Tempat Penyimpanan Rekam Medis di Rumah Sakit Pelita Insani Martapura - Ermas Estiyana; Sella Widyanti (HB PRESS, 2021)
Medical record storage management needs to consider ergonomic aspects because it facilitates work procedures in achieving work efficiency and effectiveness. This study aimed to determine the spatial ergonomic aspects of the storage area for medical records at the Pelita Insani Martapura Hospital. It was descriptive research with a qualitative approach. The subjects of this study were three respondents, namely the main informant (two medical record storage officers) and the triangulation informant (the head of medical records department). The research instruments were room thermometer, meter, and lux meter. The results showed that the temperature of the medical records storage room was 29.1 ºC, making the medical record storage officers sweat quickly and often tired in working in the medical record storage room. The size of ​​the medical record storage room was 210.88 m². All informants felt that the room was narrow, and the obstacles in the room were the hampered mobility of officers in retrieving medical records. The distance between the shelves in the medical storage room at Pelita Insani Hospital, Martapura, was as follows: 37 cm and 39 cm in the north, 58 cm in the west, and 84 cm in the south. All informants felt that the distance between the racks slowed down the staff in retrieving and returning medical records and decreased the attendant’s effectiveness. The lighting of the medical record storage room used general lighting type lamps as follows: 51 lux in the north, 73 lux in the south, 103 lux in the east, and 107 lux in the west. The lighting in the medical record storage room was not synchronous because the use of the light bulb could not be evenly distributed as a whole in each room. All informants felt that the lighting in the storage room made them difficult to find medical record files on the storage racks and misplace the medical records. The spatial ergonomic aspects of medical record storage at Pelita Insani Martapura hospital did not facilitate work procedures to become efficient and effective.